Pharmacists' knowledge, attitudes and beliefs regarding screening and brief intervention for prescription opioid abuse: a survey of Utah and Texas pharmacists. Issue 2 (21st March 2013) - Cochran, Gerald; Field, Craig; Lawson, Kenneth; Erickson, Carlton
Abstract Background In the USA prescription opioids, which are misused or abused by some patients, are often obtained from pharmacies. However, screening and brief intervention (SBI) for prescription opioid misuse has not been tested in this setting. The goal of this project was to assess pharmacists' attitudes and motivation towards delivering SBI for prescription opioid abuse. Methods A descriptive cross‐sectional online survey was administered to pharmacists in Utah and Texas, USA. The survey assessed pharmacists': (1) interest in addressing prescription opioid abuse; (2) beliefs about whether pharmacies may be effective locations to deliver SBI; and (3) potential education or training needs to facilitate SBI service delivery. Results A total of 739 pharmacists responded to the survey. Despite demographic differences, responses to the survey items were similar between Utah and Texas. The highest levels of agreement for survey subscales indicated that: (1) screening and intervention resources would increase pharmacists' motivation to deliver SBI; (2) pharmacists were interested in helping patients who misuse; and (3) pharmacists possess sufficient opioid knowledge and confidence in practice to address prescription abuse. Roughly half of pharmacists that responded agreed that SBI is a service they should deliver. Conclusion Pharmacists are interested in helping those who misuse prescription opioids and believe pharmacies may be settings in which SBI services can be tested and delivered. These results require replication to assess if they portray pharmacists' views generally. If replicated, future research could examine methods of screening and intervention in the pharmacy setting for prescription opioid misuse.